2002
DOI: 10.1007/s00586-001-0349-7
|View full text |Cite
|
Sign up to set email alerts
|

The sagittal anatomy of the sacrum among young adults, infants, and spondylolisthesis patients

Abstract: The anatomic pelvic parameter "incidence" -the angle between the line perpendicular to the middle of the sacral plate and the line joining the middle of the sacral plate to the center of the bicoxofemoral axis -has been shown to be strongly correlated with the sacral slope and lumbar lordosis, and ensures the individual an economical standing position. It is important for determining the sagittal curve of the spine. The angle of incidence has also been shown to depend partly on the sagittal anatomy of sacrum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
173
3
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(205 citation statements)
references
References 7 publications
14
173
3
15
Order By: Relevance
“…A significant difference in the sagittal pelvic and sacral morphology was already reported between the normal subjects and those suffering from a spondylolysis [4,6,12,17,22,23]. This consists of a sagittal widening of the pelvis, expressed by an increase in the values of the anatomical parameters (PI, Jackson's angle PR-S1, FSPA, STA).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A significant difference in the sagittal pelvic and sacral morphology was already reported between the normal subjects and those suffering from a spondylolysis [4,6,12,17,22,23]. This consists of a sagittal widening of the pelvis, expressed by an increase in the values of the anatomical parameters (PI, Jackson's angle PR-S1, FSPA, STA).…”
Section: Discussionmentioning
confidence: 90%
“…From this enlargement emanates an accentuation of the positional pelvic parameters (SS, PT, PA, angle SI) traducing a more tilted sacral plate. Some authors consider an important pelvic incidence as a pejorative factor for the progression of the vertebral listhesis [4,11,17]. But others did not observe it as significant [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its close relationship with the spine, many studies have investigated the influence of sacropelvic balance and morphology in the evaluation and treatment of spinal disorders, such as developmental spondylolisthesis [1][2][3][4][5][6][7][8][9][10][11][12], degenerative spondylolisthesis [13,14], adolescent idiopathic scoliosis [15][16][17], and adult spinal deformity [18][19][20]. Some authors have also raised the role of sacropelvic morphology and balance in the pathogenesis and surgical treatment of hip osteoarthritis [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the sagittal pelvic morphology greatly influences the standing balance in normal adults, especially by regulating the lumbar lordosis [11,14,15,20,22,25].…”
Section: Introductionmentioning
confidence: 99%